Assessing customer loyalty from the point of view of a tourism organiser - Pranevičienė, Vaiva; Žymantas, Paulius (Applied Scientific Research, 2022)
The article considers the theoretical dimensions of customer loyalty and the factors that shape loyalty, customer satisfaction and their perceived value. An analysis of customer loyalty assessment models was performed. The SERVQUAL model, which is widely used to assess the quality of service perceived by customers, was chosen for the empirical study. Based on this model, a questionnaire was compiled and 113 clients of a specific tourism organization were interviewed. The analysis of the results of this survey made it possible to assess the loyalty of customers to this tourism organization, to identify the main factors that encourage customers to re-use the services of a tourism organization, and the areas for improvement. Keywords: customer loyalty, tourism organizer, customer satisfaction, service quality.